Adverse events associated with human papillomavirus vaccines: a protocol for systematic review with network meta-analysis incorporating all randomised controlled trials comparing with placebo, adjuvants and other vaccines. Issue 8 (21st August 2019) - Takeuchi, Jiro; Noma, Hisashi; Sakanishi, Yuta; Kawamura, Takashi
Abstract : Introduction: Adverse events following the injection (AEFIs) of human papillomavirus vaccine (HPVv) among female adolescents are still a major public health concern. Methods: According to the Preferred Reporting Items for Systematic Reviews and Meta-Analysis extension statement for systematic reviews incorporating network meta-analyses, all prospective randomised trials will be included. The primary outcome for adverse events is topical pain during the observation period. We will mainly search 17 electronic databases from January 2000 through September 2019 with suitable Medical Subject Headings and text words for PubMed. Two reviewers will independently check the reports at the title/abstract level and identify potentially applicable studies. Then we will obtain their full texts and decide whether to include them based on the same eligible criteria. We will compare HPVv with placebo, HPVv with adjuvant and HPVv with other vaccines. Interstudy heterogeneity, publication biases or small study effects will be evaluated using conventional meta-analysis methods. The consistency of the network will be checked using tests for local and global inconsistency and the side-splitting method. To address the heterogeneity of treatment effects among the studies, we will use the multivariable random effect model. Ethics and dissemination: This pairwise or network meta-analysis does not require ethics approval. The data used here are not individual nor private. We will be able to determine which component of the vaccine induces adverse events, especially topical pain. This systematic review with network meta-analysis will provide valid answers regarding AEFIs for HPVv. PROSPERO registration number: CRD42018109265